Teachers’ Challenges in Teaching English as a Foreign Language in Vocational High School - Ulwiah, Pitrah; Noni, Nurdin; Amin, Fatimah Hidayahni (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research was conducted to determine teacher solutions to cope with the challenges of teaching English as a foreign language in vocational high schools. This research used descriptive and qualitative research. The English teacher at SMKN 5 Pangkep was chosen as the research subject. Data was collected through semi-structured interviews and non-participant observation. The results of this research show that: solutions implemented by teachers to cope with the challenges faced include improvement of teachers' speaking skills, improvement of students' basic English skills, material development, organizing time well, creating a fun classroom atmosphere, and making use of the available facilities. Therefore, these solutions are expected to be able to cope with the challenges of teaching English as a foreign language in vocational high schools.